ANALISIS KETERSEDIAAN POHON SEBAGAI PENYERAP EMISI KARBON DI KAMPUS UNNES. - Abdul, Chamid; Liesnoor, Setyowati Dewi; Tukidi, Tukidi (Geo-Image, 2018)
Emissions are substances, energy and or other components resulting from an activity which enter and or in the ambient air of stuffed into that have and or have no potential as polluter. On-campus UNNES emissions resulting from two sources, namely, from motor vehicles and the use of the genset. The population of this study is the tree and emissions. The variable in this study i.e. the distribution of the trees, the fuel consumption and carbondioxide emissions of the oil, the ability of tree in absorbing emissions. Data analysis technique use is describtive analysis, analysis of the quantity of emissions, absorptions analysis and comparison analysis. The result showedthat the area that has the most land is the Rectorat, ith a total of 10.264 tree. Total direct emissions generated in the campus UNNES is 1,395,709.52 Kg/year, and emission absorption by trees in UNNES is 6,289,250.38 Kg/year. This means that all existing on-campus area of UNNES was able to absorb the emissions it generates. This research shows that the more wide open green space then the number of trees that exist therein are also more and more, but the number of trees that many donot guarantee the magnitude of emission absorption ability on a tree because every region has different in absorbing emissions. This research shows that the more wide open green space then the number of trees that exist therein are also more and more, but the number of trees that many do not guarantee the magnitude of emission absorption ability on a every region because every tree because has different capabilities in absorbing emissions.